Enhancing the value of women's reproductive rights through community based interventions in upper Egypt governorates: a randomized interventional study - Ammal M. Metwally; Rehan M. Saleh; Lobna A. El-Etreby; Somia I. Salama; Ahmed Aboulghate; Hala A. Amer; Asmaa M. Fathy; Reham Yousry; Sherif E. El-Deeb; Ghada A. Abdel-Latif; Dalia M. Elmosalami; Nihad A. Ibrahim; et al. (BMC, 2019)
Abstract Background In 2012, the WHO described the quality of health care as the route to equity and dignity for women and children. Aim of the work To provide community based support and empowerment to women in childbearing period to seek optimal prenatal, natal and postnatal healthcare. Achieving this is anticipated to decrease maternal morbidity and mortality in Egypt. Subjects and methods An interventional study was conducted among women in childbearing period in the poorest two governorates of Upper Egypt. The study passed through three stages over three and a half years; pre-interventional assessment of awareness (n = 1000), educational interventions targeting the health providers and all women in childbearing period in their communities (n = 20,494), and post-intervention evaluation of change in awareness of their rights for prenatal, natal and postnatal care (no = 1150). Results The studied indicators relating to receiving care in pregnancy, labor, and puerperium have changed dramatically as a result of the study interventions. Results of the study showed that before interventions, the surveyed women had inaccurate knowledge regarding most of the items related to their rights. The percentages of women aware of their right to have pregnancy card increased and those who possessed a pregnancy card were doubled with a significant percent change of more than 25%. Some indicators showed more than 75% improvement, including; percent of surveyed women who knew that it's their right to follow up their pregnancy and to deliver with a specialized doctor, a trained nurse or at an equipped health facility, and those who knew their right to have at least two home preparations necessary for safe delivery at home. Conclusion and recommendations More work is needed in order to achieve the targeted reduction of maternal mortality. This could be achieved by ensuring accessible and high quality care provided by the governmental health facilities together with increasing the awareness of women regarding their rights in receiving such care.